2021
DOI: 10.3390/ijms22063256
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Toxic Concentration of Telomerase Inhibitor BIBR1532 Fails to Reduce TERT Expression in a Feeder-Free Induced Pluripotent Stem Cell Model of Human Motor Neurogenesis

Abstract: Several studies have shown that human induced pluripotent stem cell (iPSC)-derivatives are essentially fetal in terms of their maturational status. Inducing ageing in iPSC-motor neuron (MN) models of amyotrophic lateral sclerosis (ALS) has the potential to capture pathology with higher fidelity and consequently improve translational success. We show here that the telomerase inhibitor BIBR1532, hypothesised to recapitulate the telomere attrition hallmark of ageing in iPSC-MNs, was in fact cytotoxic to feeder-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has been shown that inhibiting telomerase in iPSCs using BIBR1532 followed by differentiation into midbrain dopaminergic neurons resulted in a manifestation of age-related phenotypes such as DNA damage, dendritic atrophy and mitochondrial perturbation ( Vera et al, 2016 ). Unfortunately, iPSCs and iPSC-derived MNs treated with BIBR1532 either did not survive, or, at low and well-tolerated concentrations, did not manifest age-related phenotypes ( Pandya et al, 2021 ). Thus, this approach might require further optimization, such as testing increasing treatment durations.…”
Section: Strategies To Differentiate Ipscs Into Aged Mnsmentioning
confidence: 99%
“…It has been shown that inhibiting telomerase in iPSCs using BIBR1532 followed by differentiation into midbrain dopaminergic neurons resulted in a manifestation of age-related phenotypes such as DNA damage, dendritic atrophy and mitochondrial perturbation ( Vera et al, 2016 ). Unfortunately, iPSCs and iPSC-derived MNs treated with BIBR1532 either did not survive, or, at low and well-tolerated concentrations, did not manifest age-related phenotypes ( Pandya et al, 2021 ). Thus, this approach might require further optimization, such as testing increasing treatment durations.…”
Section: Strategies To Differentiate Ipscs Into Aged Mnsmentioning
confidence: 99%
“…Nevertheless, it is important to state that the action of BIBR1532 is found to cause a severe toxic effect in various cell types. There is also evidence to indicate that in low, non-toxic doses, BIBR1532 is not effective against telomerase activity ( 15 ). However, a detailed understanding of the molecular basis of BIBR1532 inhibition will require the crystal structure analysis of the telomerase-inhibitor complex ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…These neurons did indeed show age-like characteristics including increased DNA damage, mitochondrial ROS and dendrite atrophy. However, there are limitations to using small molecules to regulate telomerase activity, and another study found BIBR1532 was unable to induce telomerase inhibition in hiPSC-derived motor neurons (Pandya et al 2021 ). To our knowledge, this study presents the first genetically modified hiPSC lines with reduced telomerase activity and shortened telomeres and thus provides a unique genetic model to induce aging characteristics.…”
Section: Discussionmentioning
confidence: 99%